An empirical investigation on factors that affecting savings behavior towards retirement planning. - Ahmad Rusly, Muhammad Shakor (2015)
Most of the Malaysian nowadays are been declare bankruptcy in early age. The main factors why they been declare as bankruptcy is because due to less saving made. The objective of this paper is to identify factors that influence saving behavior towards retirement. There are three factors had been selected as independent variable which are individul, financial literacy, and social influence. 100 of questionnaires has been distribute and the data has been analysed using Statistical Package for Socia Science (SPSS). The result of this research revealed that individual (0.000), financial literacy (0.000), and social influence (0.000) were significantly influence the saving behavior of employees around malacca.